Impact of Development-induced displacement on the Tribal community, with special reference to the women in Odisha - De, Debasree (ASEAN Journal of Community Engagement, 2020)
Anti-displacement movements are one of the burning issues in the current global scenario. Global south has been experiencing such widespread resistance since the inception of its anti-colonial struggle. Gender in this context has played a crucial part to make it a large-scale mass movement, as the women bear the brunt of displacement. It is chiefly because they have economic independence as they have customary rights over the communal property resources. Displacement has caused mental trauma for the adivasi women who end up being prostitutes to eke out livelihoods. In this background the present article seeks to explore the impact of development-induced-displacement on the adivasi women of Odisha and analyses their struggle for survival from a socio-historical point of view. The research is based on data collected during the field survey employing a stratified simple random sampling method. The objective of the present research is to understand the changing pattern of livelihood of the adivasi women before and after displacement and how they are coping with the mental trauma caused by their dispossession. In theory, it is believed that the adivasi women enjoy a greater autonomy than their non-adivasi counterparts. But the primary outcome of the research shows that, in the wake of neo-liberal economy, increasing risks of life and deteriorating standard of living due to evictions causing serious problems like loss of assets, alcoholism, wife-battering, and domestic violence. Therefore, the research attempts to analyse the plight of the adivasi women suffering due to the onslaught of destructive “development” and thus taking part in many ongoing movements against displacement.